GROWTH AND PRODUCTION Panicum maximum cv. Trichoglume IN SOIL TYPE AND DIFFERENT DOSAGE TSP FERTILIZER - I K. G., Sudiarsana; Budiasa, I K. M.; Duarsa, M. A. P. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
Reseach aimed knowing the growth and production of forage Panicum maximum cv. Trichoglume on different soil types and TSP fertilizer doses. The study was conducted at the Greenhouse in Sading Village, Mengwi District, Badung Regency, for 3 months. The design used in this study is a complete random design (CRD) of a 3 × 3 nested pattern with the treatment of soil types, namely mediterranean soil (TM), regosol soil (TR), latosol soil (TL) and fertilizer dosage namely: control (D0), 50 kg TSP/ha of (D1) and 100 kg TSP/ha of (D2). The treatment was repeated 4 times so that there were 36 experimental units. The observed variables are growth, production and growth characteristics variables.The results showed that the growth and production of forage Panicum maximum cv. Trichoglume on different soil types and TSP fertilizer doses had the highest average of latosol on growth variables ie plant height wich reached 92,63 cm but statistically not real differentcompred to mediterranean and regosol soils,production variables in latosol soil have the highest average in leaf dry weight reaching 2,34 g significantly different compared to regosol soils which reach 1,58 g, the variable growth characteristics in regosol soils have the highest average of 0,74 significantly different from latosol soils which reach 0,62.The conclusion of this research is that latosol soil provides the best growth and production in Panicum maximum cv. Trichoglumegrass,growth and production Panicum maximum cv. Trichoglume on the best type of latosol soil and mediterranean soil at a dose of 100 kg fertilizer TSP/ha, while on regosol soil at a fertilizer dose of 50 kg TSP/ha.   Key words : growth, production, Panicum maximum, soil type, TSP fertilizer